A Multigrid Solver based on Distributive Smoother and Residual Overweighting for Oseen Problems. Issue 2 (28th May 2015) - Chen, Long; Hu, Xiaozhe; Wang, Ming; Xu, Jinchao
Abstract An efficient multigrid solver for the Oseen problems discretized by Marker and Cell (MAC) scheme on staggered grid is developed in this paper. Least squares commutator distributive Gauss-Seidel (LSC-DGS) relaxation is generalized and developed for Oseen problems. Residual overweighting technique is applied to further improve the performance of the solver and a defect correction method is suggested to improve the accuracy of the discretization. Some numerical results are presented to demonstrate the efficiency and robustness of the proposed solver.